The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1259/bjr/64727750
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic fine-needle aspiration biopsy of the lungs using a C-arm cone-beam CT system: diagnostic accuracy and post-procedural complications

Abstract: Objective: The purpose of our study was to evaluate the diagnostic accuracy of transthoracic fine-needle aspiration biopsy (TFNAB) using a C-arm cone-beam CT (CBCT) system and to assess risk factors for immediate post-procedural complications in patients with lung lesions. Methods: From October 2007 to April 2009, 94 TFNAB procedures using a C-arm system were studied in 91 patients with pulmonary lesions a chest CT scans. We retrospectively reviewed the patients' radiological and histopathological findings. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
1
20
1
1
Order By: Relevance
“…Seven of the studies [14,1621] were retrospective whereas one study [15] was prospective. Of these, 4 studies [14,1628] were conducted in different medical institutions in South Korea, whereas the other 4 studies [15,1921] were conducted in different institutions all over the world. Information about the technical statements of PTNB using CBCT and other basic descriptions of the 8 articles involved in this systematic review and meta-analysis are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of the studies [14,1621] were retrospective whereas one study [15] was prospective. Of these, 4 studies [14,1628] were conducted in different medical institutions in South Korea, whereas the other 4 studies [15,1921] were conducted in different institutions all over the world. Information about the technical statements of PTNB using CBCT and other basic descriptions of the 8 articles involved in this systematic review and meta-analysis are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The selection of a biopsy procedure with a low radiation dose is important for patient’s safety. From our data extraction, it was revealed that an effective dose for CBCT-guided PTNB had been reported in all of the studies [14,15,1721] except for the study conducted by Lee et al [16]. The reported mean estimated effective patient radiation dose ranged between 4.6–14.3 mSv (mean, 7.34 mSv) [14,1821].…”
Section: Discussionmentioning
confidence: 96%
“…Braak et al [8] described the effective patient dose of CBCT guidance procedures to be reduced by 13-42% compared with CT guidance for abdominal and thoracic procedures. Other authors reported diagnostic accuracies of CBCT guidance to be comparable to or higher than other guidance modalities [14][15][16][20][21][22]. However, until now, the accuracy of CBCT guidance for reaching small (millimetre-sized) targets has not been addressed specifically.…”
mentioning
confidence: 99%
“…After the procedure, the patient has bed rest and avoid vigorous physical activity for the first 24 hours. The most frequently reported complications include: (I) Pneumothorax (5,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59): pneumothorax is the most common complication. A small pneumothorax may spontaneously resolve without any treatment.…”
Section: Complicationsmentioning
confidence: 99%